TanDEM-X: Mission Concept, Product Definition and Performance Prediction - Krieger, Gerhard; Moreira, Alberto; Fiedler, Hauke; Hajnsek, Irena; Zink, Manfred; Werner, Marian; Eineder, Michael (European Conference on Synthetic Aperture Radar (EUSAR), 2006)
This paper gives a short overview of the TanDEM-X mission concept, summarizes the basic products, illustrates the achievable performance, and gives some examples for new imaging modes.
DLR Import::2019-04-03